Adherence to Pharmacotherapy in Patients With Parkinson's Disease Taking Three and More Daily Doses of Medication - Straka, Igor; Minár, Michal; Škorvánek, Matej; Grofik, Milan; Danterová, Katarína; Benetin, Ján; Kurča, Egon; Gažová, Andrea; Boleková, Veronika; Wyman-Chick, Kathryn A.; Kyselovič, Ján; Valkovič, Peter (Frontiers in Neurology, 2019)
Background: Once-daily treatment formulation is associated with better adherence in comparison to more complex medication regimens. The study was aimed to detect the extent of adherence to pharmacotherapy in Parkinson disease (PD) patients who take a minimum of three daily doses of drugs and to identify factors associated with lower levels of adherence. Methods: The cohort was selected from non-demented PD patients. The 8-Item Morisky Medication Adherence Scale (MMAS-8), 8-Item Parkinson’s Disease Questionnaire (PDQ-8), Geriatric Depression Scale (GDS), Non-Motor Symptom Assessment Scale (NMSS), 9-Item Wearing-off Questionnaire (WOQ-9), MDS-UPDRS III (motor examination) and IV (motor complications) scales were used in this study. Results: From a total of 124 subjects, 33.9% reported a high level of adherence, 29.8% reported a medium level of adherence and 36.3% reported a low level of adherence to their pharmacotherapy. The level of non-adherence correlated with gender, longer disease duration, higher scores of PDQ-8, NMSS, WOQ-9, and MDS-UPDRS IV. Detailed analysis of NMSS demonstrated a correlation between the level of adherence and domains sleep/fatigue, mood/cognition, perceptual problems/hallucinations, attention/memory and urinary symptoms. Independent risk factors for non-adherence were excessive daytime sleepiness, anhedonia and forgetfulness. Conclusion: Non-adherence to more complicated medication regimens is frequent in PD patients and it is associated with gender, longer PD duration, poorer quality of life, frequency and severity of non-motor symptoms, and more severe motor and non-motor fluctuations. Non-adherence was predicted by non-motor symptoms including fatigue, mood disturbances, and subjective cognitive complaints.